The Role of Communication Management Within the Virtual Team in an International Projects-Based Organisation - Abdul, Omolara; Kozlovski, Eugene (Archives of Business Research, 2023)
This paper examines the practice of communication management within the different geographically spread virtual teams in the attainment of project goals in a cost-effective manner. The panel research has been carried out in UK companies working in collaboration with virtual teams from Africa. Data for the research was collected through a face-to-face interview with 6 participants from a different organisation that has an internationally spread workforce; this research concentrates on examining how the practice of communication management can lead to a successful project, this study adds together different approaches to a joint strategy. The aim of this research is to examine the practice of communication management within virtual teams and by looking at how communication is managed within projects. Then, this can help to deduce the best practice of communication that convey success to projects within virtual teams. The finding from the participants confirmed that communication management is vital to achieving timely successful results within a project. However, they identified some communication challenges, but it is clear that a plan for managing communication is missing. Additionally, virtual communication is more effective when there is occasional face-to-face communication.